DESKRIPSI OBYEK WISATA WAY PANAS DI MERAK BATIN - Eldes Safitri; Buchori Asyik; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
Tourism industry is one of appropriate facilities to increase the progrees of economic industry both lokal and global. Way Panas is one of tourism places which has the role for this case the objective of this research was to describe the tourism place of Way Panas in Merak Batin which focussed on the interest,facility,accessibility, job opportunity, manpower absorption, and local recident’s income of Merak Batin village, in Natar Subdistrict Lamsel Regency. This research was used qualitative descriptive method. The research population consisted of 25 workers of Way Panas tourism place. in order to collect the data, the writer used observation, interview, questionnaire, and documentation the data analysis is conducted by using table and percentage as basic of interpretation.the result showed that: 1) there was an interest of Way Panas tourism place which has special characteristic, that was hot water of earth. 2) the tourism place was also completed with structure and infrastructure that. were fairly avaible 3) the accessibility was achievable because the location of the place was near the capital citi of province. 4) Way Panas tourism placa of Merak Batin was used by people around to create direct businesses about 16%, 4 respondents.5) the total of employees of Merak Batin village now is 57,71%. 25 employees have worked in Way Panas tourism place 6) the was main income and side progressions after working in Way Panas tourism place. Keywords: interest, infrastructure , accessibility, working opportunity, Way Panas tourism resort, employment, income of local resident